Enamel Matrix Derivative Induces Matrix Synthesis by Cultured Human Periodontal Fibroblast Cells - Haase, H.R.; Bartold, P.M. (Journal of periodontology (1970), 2001)
Background: Periodontal wound healing and regeneration require that new matrix be synthesized, creating an environment into which cells can migrate. One agent which has been described as promoting periodontal regeneration is an enamel matrix protein derivative (EMD). Since no specific growth factors have been identified in EMD preparations, it is postulated that EMD acts as a matrix enhancement factor. This study was designed to investigate the effect of EMD in vitro on matrix synthesis by cultured periodontal fibroblasts. Methods: The matrix response of the cells was evaluated by determination of the total proteoglycan synthesis, glycosaminoglycan profile, and hyaluronan synthesis by the uptake of radiolabeled precursors. The response of the individual proteoglycans, versican, decorin, and biglycan were examined at the mRNA level by Northern blot analysis. Hyaluronan synthesis was probed by identifying the isotypes of hyaluronan synthase (HAS) expressed in periodontal fibroblasts as HAS‐2 and HAS‐3 and the effect of EMD on the levels of mRNA for each enzyme was monitored by reverse transcription polymerase chain reaction (RTPCR). Comparisons were made between gingival fibroblast (GF) cells and periodontal ligament (PDLF) cells. Results: EMD was found to significantly affect the synthesis of the mRNAs for the matrix proteoglycans versican, biglycan, and decorin, producing a response similar to, but potentially greater than, mitogenic cytokines. EMD also stimulated hyaluronan synthesis in both GF and PDLF cells. Although mRNA for HAS‐2 was elevated in GF after exposure to EMD, the PDLF did not show a similar response. Therefore, the point at which the stimulation of hyaluronan becomes effective may not be at the level of stimulation of the mRNA for hyaluronan synthase, but, rather, at a later point in the pathway of regulation of hyaluronan synthesis. In all cases, GF cells appeared to be more responsive to EMD than PDLF cells in vitro. Conclusions: EMD has the potential to significantly modulate matrix synthesis in a manner consistent with early regenerative events. J Periodontol 2001;72:341‐348.